2023
DOI: 10.4236/jss.2023.113005
|View full text |Cite
|
Sign up to set email alerts
|

Family Cohesion and Relationship Quality in Defence Force Families: Rapid Review

Abstract: Objective: Retention of serving members in the military may be increased through targeted psycho-social support of their families and dependents. This Defence funded study aimed to provide updated evidence on associations between current military service and the well-being of the member's couple and relationships, to inform policy and practice. We conducted a rapid review of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
1
0
0
Order By: Relevance
“…Fifth, this review provides a shortterm analysis of military children to non-military child, thus long-term ramifications of parental service may not be captured. Additionally, consistent with prior contemporary reviews in this field (Jiang et al, 2022;McIntosh et al, 2023), as all identified data was exclusively from North America which raises generalizability concerns. As we assessed a broad array of outcomes, drawing comparisons was challenging due to outcome variability and breadth.…”
Section: Limitationssupporting
confidence: 70%
“…Fifth, this review provides a shortterm analysis of military children to non-military child, thus long-term ramifications of parental service may not be captured. Additionally, consistent with prior contemporary reviews in this field (Jiang et al, 2022;McIntosh et al, 2023), as all identified data was exclusively from North America which raises generalizability concerns. As we assessed a broad array of outcomes, drawing comparisons was challenging due to outcome variability and breadth.…”
Section: Limitationssupporting
confidence: 70%